Association of Myopia With Microvascular Alterations in Patients With Type 2 Diabetes: An Optical Coherence Tomography Angiography Study - Wen, Xin; Li, Zijing; Xiao, Jianhui; Liu, Xuane; Zhang, Yichi; Lan, Yuqing (Frontiers in Medicine, 2021)
Purpose: To determine the association of myopia with peripapillary and macular microvasculature in eyes with type 2 diabetes using optical coherence tomography angiography (OCTA). Methods: Diabetic patients with and without diabetic retinopathy (DR) were recruited and grouped according to myopic status in this cross-sectional study. Axial length, refractive error and OCTA parameters were measured. OCTA parameters were analyzed with adjustment of confounding factors and further Bonferroni analysis was performed to determine the differences in multiple group comparisons. Results: Compared with the diabetic eyes without myopia, those with myopia had lower rate of DR (21.82% vs 35.90%, χ2=6.190, P=0.013), longer axial lengths (24.94±0.75 vs 23.16±0.64 F=311.055, P＜0.001) and reduced whole vessel density (VD) of optic nerve head (ONH) (45.89±5.76 vs 49.14±4.33, F=19.052, P＜0.001), peripapillary VD (48.75±6.56 vs 50.76±4.51, F=7.600, P=0.006) and reduced thickness of the retinal nerve fiber layer (RNFL) (95.50±12.35 vs 100.67±13.68, F=5.020, P=0.026). In eyes without myopia, the superficial vessel density (SVD) (46.58±4.90 vs 43.01±4.25; 95% CI, 1.80 to 4.61; P＜0.001), deep vessel density (DVD) (45.64±6.34 vs 42.15±6.31; 95% CI, 1.07 to 5.00; P＜0.001), and FD300 area density (50.31±5.74 vs 44.95±6.96; 95% CI, 2.88 to 7.27; P＜0.001) were significant reduced in eyes with DR(DR eyes) comparing to those without DR(NoDR eyes). In eyes with myopia, only SVD were significantly reduced in DR eyes comparing to NoDR eyes( 41.68±3.34 vs 45.99±4.17; 95% CI, 1.10 to 7.22; P=0.002). In NoDR eyes, both whole VD of ONH and Peripapillary VD demonstrated a significant decrease in eyes with myopia comparing to those without myopia (49.91±4.36 vs 45.61±6.32; 95% CI, 1.95 to 6.27; P＜0.001 and 51.36±4.24 vs 48.52±6.99; 95% CI, 0.56 to 5.11; P=0.006, respectively). Conclusions: In diabetic patients, myopic eyes exhibited lower prevalence of DR and thinner thickness of RNFL. The refractive status could possibly impact the retinal microvascular changes from NoDR to DR stage.